2017
DOI: 10.1063/1.4993888
|View full text |Cite
|
Sign up to set email alerts
|

100-period InGaAsP/InGaP superlattice solar cell with sub-bandgap quantum efficiency approaching 80%

Abstract: InGaAsP/InGaP quantum well (QW) structures are promising materials for next generation photovoltaic devices because of their tunable bandgap (1.50–1.80 eV) and being aluminum-free. However, the strain-balance limitations have previously limited light absorption in the QW region and constrained the external quantum efficiency (EQE) values beyond the In0.49Ga0.51P band-edge to less than 25%. In this work, we show that implementing a hundred period lattice matched InGaAsP/InGaP superlattice solar cell with more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The incorporation of QWs or QDs can enhance the I SC , but also can lead to voltage degradation. The inclusion of 100 depleted QWs of GaInAsP/GaInP of 0.8 μm thickness on GaInP SC has boosted the I SC density up to 20.5 mA cm −2 , [ 40 ] whereas our work presents InP QW models with only 9 QWs in the p–i–n region and increases the I SC density up to 22.18 mA cm −2 . Experiment has shown that the InGaAsN/GaAs multiple QW‐based GaAs SJ SC increases the I SC , but at the same time also reduces the open circuit voltage.…”
Section: Introductionmentioning
confidence: 95%
“…The incorporation of QWs or QDs can enhance the I SC , but also can lead to voltage degradation. The inclusion of 100 depleted QWs of GaInAsP/GaInP of 0.8 μm thickness on GaInP SC has boosted the I SC density up to 20.5 mA cm −2 , [ 40 ] whereas our work presents InP QW models with only 9 QWs in the p–i–n region and increases the I SC density up to 22.18 mA cm −2 . Experiment has shown that the InGaAsN/GaAs multiple QW‐based GaAs SJ SC increases the I SC , but at the same time also reduces the open circuit voltage.…”
Section: Introductionmentioning
confidence: 95%
“…The first proposal of quantum well solar cells was reported in 1990 [ 15 ]. Thereafter, different types of quantum well solar cells have been proposed and analyzed from experimental and theoretical studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. A general feature of quantum wells is that absorption and recombination processes can be controlled through discrete eigenstates depending on well thickness and depth, allowing for finding the conditions that would result in an improved device performance.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of nanostructures such as quantum wells (QWs) to bulk material has been shown to be a potential route to improve device efficiency since it allows the absorption of extra photons with energies lower than the bulk bandgap [8][9][10][11]. That is, when QWs are embedded within an absorber material so that a type I band-alignment is formed, the quantum confinement allows the formation of discretized energy levels, extending the light absorption domain to energies lower than that of the absorber band-gap.…”
Section: Introductionmentioning
confidence: 99%
“…QW solar cells (QWSCs) have received a great deal of attention from the scientific community since their proposal in 1990 [11]. QWSCs based on different compounds have been studied to achieve efficiencies higher than the ones obtained in solar cells without the inclusion of wells [8][9][10][11][12][13]. The addition of tin sulfide selenide (SnSSe) nanostructures in the form of QWs into SnS material constitutes a potential solution to the problem of low solar cell efficiency values.…”
Section: Introductionmentioning
confidence: 99%